Transition-Metal-Catalyzed Ketone α-Alkylation and Alkenylation with Simple Alkenes and Alkynes through a Dual Activation Strategy - Lim, Hee Nam; Xing, Dong; Dong, Guangbin (Synlett, 2019)
In this personal account, we summarize our investigations on the α-alkylation and α-alkenylation reactions of ketones with nonactivated alkenes and alkynes, respectively. The serendipitous discovery of C–H alkylation/alkenylation of cyclic 1,2-diketones provided a proof of concept for a dual activation strategy. Extension to the α-alkylation and α-alkenylation of regular ketones was achieved by using 7-azaindoline as a bifunctional ligand. Subsequently, intramolecular coupling between ketones and olefins was achieved with Rh- and Ru-based systems, respectively. Finally, branched-selective α-alkylation was achieved through an Ir-catalyzed enamide-mediated C–H alkylation.1 Introduction2 Serendipitous Discovery of α-Alkylation and α-Alkenylation of 1,2-Diketones through Enamine-Mediated C–H Activation3 Intermolecular Ketone α-Alkylation of Regular Ketones with Nonactivated Olefins4 Intermolecular Ketone α-Alkenylation of Regular Ketones with Nonactivated Alkynes5 Intramolecular Ketone α-Alkylation of Regular Ketones with Nonactivated Olefins6 Branched-Selective α-Alkylation of Regular Ketones with Nonactivated Olefins7 Conclusions and Outlook
Keywords: ketones; alkylation; alkenylation; directing groups; bifunctional catalysis; C-H activation